2014
DOI: 10.1039/c4gc00025k
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free cross-coupling reaction of aldehydes with disulfides by using DTBP as an oxidant under solvent-free conditions

Abstract: A DTBP-promoted C–H thiolation of aldehydes with disulfides under metal-free and solvent-free conditions is described. The system shows good functional group tolerance to afford thioesters in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…[8] Metalf ree acyl radical engaged thioester formation processb ye mploying widely availablea ldehydes as radical coupling progenitors [9] hasl ong been investigateds ince the seminalw ork by Takagi. However,stoichiometric radical initiators, [11] or oxidants [12] are essen-tial for effective radical generation (Scheme 1a). However,stoichiometric radical initiators, [11] or oxidants [12] are essen-tial for effective radical generation (Scheme 1a).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[8] Metalf ree acyl radical engaged thioester formation processb ye mploying widely availablea ldehydes as radical coupling progenitors [9] hasl ong been investigateds ince the seminalw ork by Takagi. However,stoichiometric radical initiators, [11] or oxidants [12] are essen-tial for effective radical generation (Scheme 1a). However,stoichiometric radical initiators, [11] or oxidants [12] are essen-tial for effective radical generation (Scheme 1a).…”
mentioning
confidence: 99%
“…[15] Nonetheless, they mediated HATg enerally carried out under UV light. [4,11,12] Our exploratory studies began with am odel reaction of aldehyde 1a (0.2 mmol) with commonlyu sed sulfenyl donors (0.24 mmol) including thiol, disulfide and thiosulfonate S-ester 2a in the presence of ak etone catalyst( 0.01 mmol) in MeCN (2.0 mL) irradiated with blue LEDs under N 2 atmosphere (Table 1). [16] Studies have shown that bond dissociation enthalpy (BDE) considerations are less important than CÀHb ond polarity in HAT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our research group reported the copper‐ and iron‐catalyzed coupling of aldehydes with thiols in water by using tert ‐Butyl hydroperoxide (TBHP) as an oxidant . Very recently, we have also reported a metal‐ and solvent‐free direct C–H thiolation of aldehydes promoted by Di‐ tert ‐Butyl peroxide (DTBP) . This system showed good functional group compatibility with electron‐donating and electron‐withdrawing groups and also with halo groups, as they are all tolerated by the reaction conditions employed.…”
Section: Introductionmentioning
confidence: 99%